Surgical corridors to foramen magnum meningiomas: a mini-review - Baldoncini, Matias; Luzzi, Sabino; Almeida, Joao P.; Contreras-López, William Omar; La Corte, Emanuele; Ordóñez-Rubiano, Edgar G.; Campero, Alvaro (Frontiers in Neurology, 2023)
Gross-total resection of foramen magnum meningiomas remains the gold standard of treatment and should be performed whenever possible. The transcondylar approach (and its variations) represents the most used approach for meningiomas located in the lateral or anterior borders of the foramen magnum. Endoscopic transclivus approaches represent a useful option in selected cases of anterior midline foramen magnum meningiomas, to be performed in centers with advanced experience in endoscopic skull base surgery, with the caveats of increased risk of postoperative cerebrospinal fluid leak. Alternatively, radiosurgery remains an option for well-selected cases, especially for the management of asymptomatic patients with small enlarging tumors. Advances in molecular profiling, as well as genetic analysis, may guide adjuvant treatment.